High Grazing Pressure of Geese Threatens Conservation and Restoration of Reed Belts - Bakker, Elisabeth S.; Veen, Ciska G. F.; Ter Heerdt, Gerard J. N.; Huig, Naomi; Sarneel, Judith M. (Frontiers in Plant Science, 2018)
Reed (Phragmites australis (Cav.) Trin. ex Steud.) beds are important habitat for marsh birds but are declining throughout Europe. Increasing numbers of the native marsh bird, the Greylag goose (Anser anser L.), are hypothesized to cause reed bed decline and inhibit restoration of reed beds, but data are largely lacking. In this study, we experimentally tested the effect of grazing by Greylag geese on the growth and expansion of reed growing in belts along lake shorelines. After 5 years of protecting reed from grazing with exclosures, reed stems were over four-fold denser and taller than in the grazed plots. Grazing pressure was intense with 50-100% of the stems being grazed among years. After 5 years of protection we opened half of the exclosures and the geese immediately grazed almost 100% of the reed stems. Whereas this did not affect the reed stem density, the stem height was strongly reduced and similar to permanently grazed reed. The next year geese were actively chased away by management from mid-March to mid-June, which changed the maximum amount of geese from over 2300 to less than 50. As a result, reed stem density and height increased and the reed belt had recovered over the full 6 m length of the experimental plots. Lastly, we introduced reed plants in an adjacent lake where no reed was growing. After two years, the density of the planted reed was six to nine-fold higher and significantly taller in exclosures compared to control plots where geese had access to the reed plants. We conclude that there is a conservation dilemma how to preserve and restore reed belts in the presence of high densities of Greylag geese as conservation of both reed belts and high goose numbers seems not feasible. We suggest that there are three possible solutions for this dilemma: (1) effects of the geese can be mediated by goose population management, (2) the robustness of the reed marshes can be increased, and (3) at the landscape level, by spatial planning through landscape configuration where large reserves with reed beds are surrounded by unmown, unfertilised meadows.